A 133-year record of eutrophication in the Chaihe Reservoir, Southwest China. (January 2022) - Sun, Wenxian; Niu, Xiaoyin; Teng, Haowei; Ma, Yanfei; Ma, Longchao; Liu, Yizhou
Highlights: TOC, TN, TP, TS, and δ 13 C in the Chaihe Reservoir sediment, a plateau lake in China, were studied. The sedimentary records of TOC, TN, TP, TS imply trends in eutrophication. C/S, C/P, and N/P ratios can reflect evolution of trophic conditions in water body. Endogenous and exogenous inputs were sources of organic matter in the sediment. The eutrophic process was associated with socioeconomic development and natural changes. Abstract: In order to reveal eutrophication evolution, radionuclides ( 210 Pb and 137 Cs), total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), total sulphur (TS) concentrations, stable carbon isotope (δ 13 C) were analyzed in a sediment core collected from Chaihe Reservoir in Kunming, Yunnan province, southwest China during 2019. The results showed that the 210 Pbex activities ranged from 9.67 to 130.72 Bq/Kg (average 61.84 Bq/Kg), and the age sequence ranged from 1885 to 2018. The sediment accumulation rates were in the range of 0.04–1.85 cm/yr, with an average of 0.56 cm/yr and exogenous inputs have been increasing. Based on the nutrients (C, N, P, and S), the aquatic environment in the reservoir experienced a shift from near-natural status to human interference status. In particular, human activities has increased the input of C, N, and S into the aquatic environment in the recent years. Elemental ratios reflected that aquatic environment in the reservoir was obviously restricted by N. Additionally, oxygen concentration decreased in the sediment, corresponding to the aggravated eutrophication in the reservoir. The algae, CAM plants, and bunchless fibrous plants inputs primarily accounted for the sources of organic matter in the sediment. Ecological risk assessment showed that eutrophic ecological risk caused N in the sediment has continuously increased, whereas eutrophic ecological risk caused P has been decreased in recent years. These findings implied that eutrophication in the reservoir has been aggravated.